(untitled) (Bangladesh Journal of Dental Research & Education, 2013)
Surgical exposure of impacted upper incisor is very complex, so fixed orthodontic treatment rehabilitation is the first choice of the treatment for the correction of malocclusion. A clinical case report a 10-year old boy with a unerupted malposed upper left central incisor, which was treated by sequential surgical exposure and fixed orthodontic treatment. The tooth was aligned in the dental arch with accepted aesthetic and functional satisfaction of the patient. DOI: http://doi.dx.org/10.3329/bjdre.v2i2.16249 Bangladesh Journal of Dental Research & Education Vol.2(2) 2012: 69-70